Early Continence After Open and Laparoscopic Radical Prostatectomy With Sutureless Vesicourethral Alignment: an Alternative Technique, 8 Years' Experience - Simforoosh, Nasser; Javaherforooshzadeh, Ahmad; Aminsharifi, Alireza; Tabibi, Ali (Urology Journal, 2009)
Introduction: We reviewed urinary outcomes after sutureless vesicourethral alignment in open radical prostatectomy (ORP) and laparoscopic radical prostatectomy (LRP). Materials and Methods: Charts of 324 patients who underwent sutureless ORP (n = 188) and LRP (n = 136) were reviewed. After prostatectomy, a 22- to 24-F silicon Foley catheter was passed into the bladder via the preserved bladder neck. The Foley balloon was filled, and mild traction was applied to appose the bladder neck to the urethral stump. The Foley catheter was fixed to the patient's leg. No cystostomy was placed. Results: The follow-up period ranged from 12 to 60 months. The mean operative time was 65 minutes in ORP and 260 minutes in LRP. Blood transfusion was significantly less frequent with LRP (9.6% versus 19.7%, P = .02). The mean postoperative catheterization durations were 12 days in ORP and 13 days in LRP. Complete continence was achieve in 293 patients (90.4%) after 3 months of follow-up (88.9% in LRP and 91.5% in ORP, P = .78). The continence rate improved to 96.3% in LRP and 95.2% in ORP at 1 year (P = .52). Bladder neck stricture rate was 13.6% (12.8% in ORP versus 14.7% in LRP, P = .87). Conclusion: Sutureless vesicourethral alignment during ORP and LRP is a promising approach with minimum urinary extravasation, a high rate of continence, and an acceptable rate of stricture. This technique could be considered as an alternative in anatomically demanding situations.